Depression readmission risk is elevated in multiple sclerosis compared to other chronic illnesses. (January 2022) - Schorr, Emily M; Kurz, Daniel; Rossi, Kyle C; Zhang, Margaret; Yeshokumar, Anusha K; Jette, Nathalie; Dhamoon, Mandip S
Objective: Assess readmissions for depression or suicide attempt (SA) after MS admission versus other chronic inflammatory illnesses. Methods: This retrospective cohort study identified MS, asthma, rheumatoid arthritis (RA), depression, and SA in the 2013 National Readmissions Database by International Classification of Diseases codes. Index admissions (MS, n  = 7698; asthma, n  = 93, 590; RA, n  = 3685) and depression or SA readmission rates were analyzed. Hazard ratios (HRs) estimated 1-year depression/SA readmission hazard, comparing MS to asthma or RA, adjusting for age, sex, psychiatric comorbidity, substance abuse, tobacco use, income, and index hospitalization characteristics. Results: MS had more baseline depression (24.7%) versus asthma (15.6%) and RA (14.6%). Ninety-day depression readmission rate was higher in MS (0.5%) than asthma (0.3%) and RA (0.03%). Depression readmission HR was higher after MS admission versus asthma (HR = 1.37, 95% confidence interval (CI) = 1.00–1.86, p  = 0.0485) and RA (HR = 4.68, 95% CI = 1.60–13.62, p  = 0.0047). HR was not different for SA readmission across groups. Depression readmission HR was more than double in MS patients with psychiatric disease or substance abuse versus RA or asthma patients with either comorbidity. Conclusion: Depression readmission risk after MS hospitalization was elevated versus asthma/RA. Substance use and baseline psychiatric comorbidity were more strongly associated with depression readmission in MS patients.